Metal Mining Facts - 2001 (The National Institute for Occupational Safety and Health (NIOSH), 2003)
1. In 2001, a total of 281 metal mining operations reported employment to the Mine Safety and Health Administration (MSHA) (down from 309 metal mines in 2000). Metal mines were the smallest mining sector, 1 comprising 1.9% of all mining operations. This was the lowest percentage of all mining sectors. • The median number of operator employees per metal mine was 17.5.2 • Gold mines comprised 43.1% (n = 121) of all metal mining operations. Other types of metal mines were copper ore (n = 37, 13.2%), iron ore (n = 27, 9.6%), and lead and/or zinc ore (n = 24, 8.5%). • Nearly 20% (n = 55) of metal mines were located in Nevada.